RANCANG BANGUN SISTEM MONITORING PADA PERHITUNGAN PRODUKSI SEMEN - Miko Rizal Imasura; RA Suwodjo Kusumoputro; Mohammad Fathoni (AITI, 2016)
Technological developments in the electronics industry at this time can be quite fast, but not so in companies engaged in the production of cement. The absence of the slow process of monitoring and reporting process (report) makes the process less efficient cement production, especially on the side of labor and time. To solve the problem it was designed Monitoring System In Cement Production Calculation. This design has several components supporting the IR Proximity sensor, DCmotor, RS232 to RS485 interface, microcontroller and computer servers. When the cement production starts, the server computer will enter the desired amount of production, through serial communication with RS232 to RS485 interface microcontroller will then run as a dc motor driving the conveyor and count the number of goods being produced using IR proximity sensors, the calculation process will be sent back to the computer server for process monitoring. Once the calculation is complete microcontroller will automatically stop the production process by setting a logic low on the dc motor. Through a server computer, a report will be made based on the results of monitoring of the cement production processthat has been implemented.